The political economy of disability in South Africa, between social grants and job-creation programmes - (:unkn) unknown (My University, 2020)
While previous studies focusing on disability in South Africa have mostly discussed the programme of disability grants, this article examines the interface between disability, social welfare and the labour market in the post-apartheid society. On this basis, it shows how the pressure on people with disabilities to work is framed in a progressive recognition of their right to work and agency. However, ethnographical study cases reveal the extent to which the experience of work faced every day by people with physical disabilities in a Coloured township remains disempowering and frustrating. Based on these observations, the conclusion suggests that the current system of disability grants and job creation programmes keeps many people with disabilities in a liminal situation, since the state considers them fit and unfit for work at the same time, claiming to reintegrate them into the workforce while failing to offer them long-term employment.
Keywords: African Research